Music in the “Barb Sanders” dream series - Markert, Bettina; Schredl, Michael (Dreaming, 2024)
Music is important to humans; therefore, we would expect according to the continuity hypothesis that dreaming reflects the waking-life musical activity of the person. In this study, we analyzed the long dream series of “Barb Sanders,” who has music as one of her main hobbies. This dream series includes 4,254 dreams recorded between 1960 and 2001. Our results indicated that 13.9% of all dreams contained references to music. The most commonly occurring topics in dreams were general musical themes (e.g., dancing) and listening to music, but making music and singing were also reported. Notably, the instruments most frequently appearing in the dreams corresponded to those which the dreamer played in her waking life. The emotional context of musical dreams was mainly positive and associated with joy and happiness. Overall, the findings align with the continuity hypothesis, highlighting reflections of active musical engagement in the dream content. Future directions in dream research may explore the use of long dream series to delve into the associations between musical dream frequency as well as emotions across musicians with varying musical proficiency. (PsycInfo Database Record (c) 2024 APA, all rights reserved)